Overweight/obesity and associated cardiovascular risk factors in sub-Saharan African children and adolescents: a scoping review - Choukem, Simeon-Pierre (Int J Pediatr Endocrinol, 2020)
INTRODUCTION: Recently, childhood and adolescence overweight/obesity has increased disproportionately in developing countries, with estimates predicting a parallel increase in future cardiovascular disease (CVD) burden identifiable in childhood and adolescence. Identifying cardiovascular risk factors (CVRF) associated with childhood and adolescence overweight/obesity is pivotal in tailoring preventive interventions for CVD. Whilst this has been examined extensively in high-income countries, there is scant consistent or representative data from sub-Saharan Africa (SSA). OBJECTIVE: This scoping review synthesises contemporary studies on CVRF associated with overweight and obesity in SSA children and adolescents to provide evidence on the current burden of overweight/obesity and CVD in this population. METHODS: We searched MEDLINE and Google Scholar up to July 31, 2019 for observational and experimental studies and systematic reviews addressing childhood and adolescence overweight/obesity and CVRF in SSA without language restriction. Four investigators working in four pairs, independently selected and extracted the relevant data. The methodological quality of all included studies was assessed. RESULTS: We included 88 studies with a total of 86,637children and adolescents from 20 SSA countries. The risk of bias was low in 62 (70.5%), moderate 18 (20.5%), and high in eight (9%) studies. Overweight/obesity in SSA children and adolescents is rising at an alarming rate. Its main associations include physical inactivity, unhealthy diets, high socio-economic status, gender and high maternal body mass index. Identified CVRF in overweight/obese SSA children and adolescents are mainly metabolic syndrome, hypertension, dyslipidaemia, diabetes and glucose intolerance. There is a dearth of guidelines or consensus on the management of either childhood overweight/obesity or CVRF in overweight/obese SSA children and adolescents. CONCLUSION: The current findings suggest an urgent need to review current health policies in SSA countries. Health education and transforming the current obesogenic environment of the SSA child and adolescent into one which promotes physical activity and healthy dietary habits is required.